Advanced Toll Plaza Monitoring by Utilization of WSN Modules - Deepika, R; A.Kalpana, R; Meera, S; Sharmikha Sree, R (International Journal of Engineering and Technology, 2018)
An innovative model that goals to design, develop and instrument by utilization of WSN modules for improved form of toll collection structure. In the proposed system when the user approaches to the payment lane, the Xbee wireless transceiver receives the signal that the automobile has arrived at the payment lane, then automatically the unique id of the passenger that is the Vehicle ID has been read via on-board unit, which will be attached to every motor vehicle and collects the day-to-day toll price for that particular route. The system is employed to every motor vehicles at the time of the registration of new vehicles or it can be attached in old vehicles. This system tends to cuts the time periods for paying the toll at faster rate rather than waiting in enormous queues. If the Vehicle crosses the toll without paying toll bill less than three times, the gasoline valve of the motor vehicle is locked using relay with the support of on-board unit.Â Â